СПЕЦИФІКА КОНТАКТІВ УКРАЇНСЬКИХ ТА ЮГОСЛАВСЬКИХ ВЧЕНИХ У 50–80-ті РОКИ ХХ ст. - Саган, Галина (Київські історичні студії, 2016)
У статті в результаті вивчення нових архівних документів розкрито напрями, особливості й форми співпраці між українськими та югославськими вченими. З’ясовано вплив державної політики як УРСР, так і СФРЮ на зміст контактів. Показано значення особистісного фактору в розгортанні зв’язків між вченими. Відзначено, що нехтування інтересами останніх, відсутність належної уваги до наукових інституцій з боку влади негативно відображається на міжнародному авторитеті країни та дієвості її керівництва. В статье в результате изучения новых архивных документов раскрыты направления, особенности и формы сотрудничества между украинскими и югославскими учеными. Выяснено влияние государственной политики как УССР, так и СФРЮ на содержание контактов. Показано значение лично стного фактора в развертывании связей между учеными. Отмечено, что пренебрежение интересами последних, отсутствие должного внимания к научным институциям со стороны власти негативно отражается на международном авторитете страны и действенности ее руководства. Modern integration processes require strong contacts with the international community in all areas of social development. Science as an engine of progress should take the leading position to hold the overall progress of the country. Experience, that Ukrainian scientifi c organizations have, is quite important in the search for new directions and forms of cooperation. The purpose of this study is to explore a similar experience that has accumulated, as a result of contacts between Ukrainian scientists and Yugoslav scientists during 50–80s of the 20th century. The relevance of this study is enhanced by the fact that the current relations of Ukraine with the newly independent countries that emerged on the post-Yugoslav territory are very scanty, comparing with the second half of the 20th century. Thus, the study of the past experience should help overcome the current shortage of relations with Balkan countries. In general, during the post-war period up to the 90s of the 20th century Yugoslav and Ukrainian scientists have collaborated in various fi elds of scientifi c knowledge, but it is fair to say, however, that these contacts were not regular and the potential of both sides was used only partially. Successful results were achieved primarily in agriculture. The result of international cooperation, in the mid 60s of the 20th century, was the introduction of a new method (Coconut palmettos) of fruit trees formation (gardens in the 34 farms of the Crimea). In 80s of the 20th century Novisadskii and Zemunskii Research Centers had a possibility to share new developments of breeding with the Kharkiv Institute of Plant Production, Breeding and Genetics and with the Odesa All-Union of Selection and Genetics Institute. Universities of Ukraine and SFRY established contacts in the scientifi c fi eld. Specifi cally the cooperation was developed between the universities of Kharkiv and Sarajevo, Novi Sadu and Uzhgorod, Kyiv and Zagreb. During the 60–80s of the 20th century, the most productive relationships were between Taras Shevchenko National University of Kyiv and University of Zagreb. During this period it was sent 52 teachers and 197 students from Kyiv to Zagreb University. Accordingly, KNU received 60 teachers and about 200 students from Zagreb. The level of cooperation between Yugoslav and Ukrainian philologists among other things demonstrates the results of translation activity. In particular, during the Soviet system works of Yugoslav authors were published 78 times a total circulation of more than 3.8 million copies. Certainly, Yugoslavia was ready to deepen cooperation with scientifi c institutions of Ukraine. However, the closed nature of the USSR’s research institutions and limited access to the world stage forced SFRY to cut plans for cooperation with Ukrainian counterparts. Basically, instead of direct communication scientists were forced to be limited in acquaintance with each other’s successes through the scientifi c literature, which with less obstacles got to Yugoslavia and Ukraine.